2020
DOI: 10.1371/journal.pone.0242575
|View full text |Cite
|
Sign up to set email alerts
|

Adequately iodized salt is an important strategy to prevent iodine insufficiency in pregnant women living in Central Java, Indonesia

Abstract: Iodine is an essential micronutrient for cognitive development and growth. Optimal intakes are critical during pregnancy. We report the iodine status and thyroid function of pregnant women living in areas previously affected by severe iodine deficiency and in longstanding iodine sufficient areas in Java, Indonesia. This cross-sectional study was conducted in Magelang, Java, from July to November 2015, in four sub-districts; two previously affected by severe iodine deficiency (area 1) and two that were iodine-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Mothers participated in this study were the same as the study on iodine sufficiency among pregnant women in the previous years. Simple random sampling was used to determine the participants of the research [15]. The sampling frame for this study was 244 mothers which completed the earlier year study, 213 of them complete the pregnancy until having babies and complete this study.…”
Section: Methodsmentioning
confidence: 99%
“…Mothers participated in this study were the same as the study on iodine sufficiency among pregnant women in the previous years. Simple random sampling was used to determine the participants of the research [15]. The sampling frame for this study was 244 mothers which completed the earlier year study, 213 of them complete the pregnancy until having babies and complete this study.…”
Section: Methodsmentioning
confidence: 99%
“…Rajput et al and Kusrini et al studied pregnant women who did not consume iodine-containing vitamins and minerals and they found that UIE decreased with increasing gestational age [16], [24]. Further research is needed to link mercury contamination levels, iodine status, and salt consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a study in suburb area of Central Java, Indonesia, showed that 13.8% of pregnant women had low median urinary iodine concentration (<150 μg/L), this proportion increased in each trimester. The biggest source of daily iodine consumption was iodized salt, while food sources of iodine were less consumed in pregnant women ( 123 ). The previous study confirmed that iodized salt and daily supplementation of iodine capsules had similar effects in determining the iodine status and thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%